Digital archiving for interdisciplinary knowledge transfer in intangible heritage - Sum, Hedren Wai Yuan (2018)
“Exploring the crossroads of linguistic diversity: language contact in Southeast Asia” is an interdisciplinary project with a disparate team of 11 researchers from linguistics, art, design and media. A range of digital assets in different formats, including publications, films and datasets, were created from the fieldwork and research done. Using this project as a case study, this paper seeks to explore an approach on how digital assets from an interdisciplinary research project can be captured, preserved and (re)presented in a form of a digital archive. It results in a digital archive with dedicated views for each type of digital asset to meet specific viewing needs. It also used a modular design approach to achieve flexibility and meet the knowledge transfer objectives of the research project.